Disproportionate left atrial myopathy in heart failure with preserved ejection fraction among participants of the PROMIS-HFpEF study - Ravi B. Patel (Nature Portfolio, 2021)
Abstract Impaired left atrial (LA) function in heart failure with preserved ejection fraction (HFpEF) is associated with adverse outcomes. A subgroup of HFpEF may have LA myopathy out of proportion to left ventricular (LV) dysfunction; therefore, we sought to characterize HFpEF patients with disproportionate LA myopathy. In the prospective, multicenter, Prevalence of Microvascular Dysfunction in HFpEF study, we defined disproportionate LA myopathy based on degree of LA reservoir strain abnormality in relation to LV myopathy (LV global longitudinal strain [GLS]) by calculating the residuals from a linear regression of LA reservoir strain and LV GLS. We evaluated associations of disproportionate LA myopathy with hemodynamics and performed a plasma proteomic analysis to identify proteins associated with disproportionate LA myopathy; proteins were validated in an independent sample. Disproportionate LA myopathy correlated with better LV diastolic function but was associated with lower stroke volume reserve after passive leg raise independent of atrial fibrillation (AF). Additionally, disproportionate LA myopathy was associated with higher pulmonary artery systolic pressure, higher pulmonary vascular resistance, and lower coronary flow reserve. Of 248 proteins, we identified and validated 5 proteins (involved in cardiomyocyte stretch, extracellular matrix remodeling, and inflammation) that were associated with disproportionate LA myopathy independent of AF. In HFpEF, LA myopathy may exist out of proportion to LV myopathy. Disproportionate LA myopathy is a distinct HFpEF subtype associated with worse hemodynamics and a distinct proteomic signature, independent of AF.